Empowering cadres: the impact of KEPITING, a web-based application on stunting knowledge and attitudes - Kurniawan, Novan; Mulyono, Sigit; Fitriyani, Poppy; Yulianti, Eka Putri (Jurnal Ners, 2025)
Introduction: Stunting, an indicator of chronic malnutrition, affects children under five. Cadres hold strategic positions to enhance this. Despite the launch of digital applications designed to address stunting by enhancing knowledge and attitudes, their lasting impacts and usability have not been thoroughly evaluated, especially among cadres. Methods: We conducted a longitudinal study to evaluate the long-term impact and usability of our web-based app KEPITING (Kader Peduli Stunting) to enhance knowledge and attitudes towards stunting detection among cadres covering two Districts in Jambi. We obtained 152 cadres as participants using purposive sampling, separated into two groups based on their respective districts—one using KEPITING and the other traditional training materials. Data were collected at pre-intervention, post-intervention, and nine months post- intervention using validated questionnaires to assess knowledge and attitude changes. A generalized Linear Model with Repeated Measures ANOVA and Mann-Whitney U tests was employed to examine the effects and interactions. Results: KEPITING significantly improved knowledge of practical procedures (p <0.001) and nutritional interventions (p <0.001). Overall attitude improved significantly (p = 0.008, η = 0.033). Knowledge retention showed no significant time effect, whereas attitudes improved over time and were better retained in the intervention group. The System Usability Scale scored below an average of 58.7, indicating that usability improvements were needed. Conclusions: KEPITING enhances cadre knowledge and attitudes but requires usability enhancements for optimal impact. This study highlights the importance of digital tools in stunting interventions and suggests areas for future research focusing on usability and long-term efficacy.